2012
DOI: 10.1088/0957-4484/23/47/475201
|View full text |Cite
|
Sign up to set email alerts
|

Tunable bandgap energy of fluorinated nanocrystals for flash memory applications produced by low-damage plasma treatment

Abstract: A plasma system with a complementary filter to shield samples from damage during tetrafluoromethane (CF(4)) plasma treatment was proposed in order to incorporate fluorine atoms into gadolinium oxide nanocrystals (Gd(2)O(3)-NCs) for flash memory applications. X-ray photoelectron spectroscopy confirmed that fluorine atoms were successfully introduced into the Gd(2)O(3)-NCs despite the use of a filter in the plasma-enhanced chemical vapour deposition system to shield against several potentially damaging species. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…The slits on the upper plate are aligned with the stripes on the lower plate, which can block high-energy collimated ions and prevent direct exposure of the samples to UV radiation. In our previous study [27,28], we confirmed that the UV intensity can be reduced by more than 95%. Therefore, the filter can efficiently shield the samples from plasma damage caused by energetic ions and UV radiation.…”
Section: Methodssupporting
confidence: 76%
See 1 more Smart Citation
“…The slits on the upper plate are aligned with the stripes on the lower plate, which can block high-energy collimated ions and prevent direct exposure of the samples to UV radiation. In our previous study [27,28], we confirmed that the UV intensity can be reduced by more than 95%. Therefore, the filter can efficiently shield the samples from plasma damage caused by energetic ions and UV radiation.…”
Section: Methodssupporting
confidence: 76%
“…In our previous studies, we developed a low-damage plasma treatment (LDPT) method for the functionalization of nanocrystalline and thin-film materials for applications in flash memory devices and ion sensors, respectively [27,28]. Both results demonstrated successful functionalization with minimal plasma damage.…”
Section: Introductionmentioning
confidence: 99%
“…After the Au-NPs had formed, a 20-nm-thick SiO 2 layer was deposited via plasma-enhanced chemical vapor deposition (PECVD) as the BO layer, where the samples were kept in a SiH 4 and N 2 O ambient at a radio frequency (RF) power of 50 W with gas flow rates of 5 and 200 sccm, respectively. Thereafter, a low-damage CF 4 plasma treatment was performed in a PECVD system with a quartz filter, filtering high-energy electrons, ions, and ultra-violet (UV) radiation to reduce plasma damage on the BO layer [ 15 ]. The chamber was first evacuated to 10 −6 Torr and gradually heated to 300 °C.…”
Section: Methodsmentioning
confidence: 99%